2021
DOI: 10.1093/jscr/rjaa582
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous trans-anal evisceration of small bowel: a case report

Abstract: Trans-anal evisceration of small bowel is a rare surgical presentation. The first case ever reported was in 1827. The exact mechanism of how this develops remains poorly understood. A 70-year-old lady presented with multiple small bowel loops eviscerated through the anus. Abdominal exploration was done. The bowel was carefully reduced. There was a longitudinal defect on the anterior wall of the rectum at the recto-sigmoid junction and a large mesenteric defect and thrombosed mesenteric vessels c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…Spontaneous rectal perforations with transanal small bowel herniation are extremely rare emergencies with a dramatic clinical presentation. Less than 100 cases have been published since the first description in the literature by Brodie in 1927 2–5. In most of these cases, small intestine is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous rectal perforations with transanal small bowel herniation are extremely rare emergencies with a dramatic clinical presentation. Less than 100 cases have been published since the first description in the literature by Brodie in 1927 2–5. In most of these cases, small intestine is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reviews by Wrobleski and later Morris, spontaneous small bowel evisceration per rectum occurs more frequently among elderly women, some having rectal and uterine prolapse concurrently [1] , [5] , [6] , [7] . Although the exact etiology of this phenomenon is not clearly known, chronic rectal prolapse has been linked to this pathology as a predisposing factor [3] , [8] , [9] , [10] , [11] . In some cases, however, like our case, the patients did not have any history of rectal prolapse [1] , [12] , [13] , [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Although several authors reported successful outcomes without colostomy, there were no mortality in cases managed with Hartmann's procedure. Simultaneous treatment of the causative factor such as rectopexy for rectal prolapse should also be considered [1] , [3] , [11] , [13] , [20] If left untreated, this condition has 100% mortality, but with proper treatment the mortality rate is reduced significantly [2] . It is suggested that to prevent this rare condition, its predisposing factors such as rectal prolapse and uterine prolapse should be treated before the development of complications, especially in elderly patients [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9cases were caused by transanal suction from a swimming pool drain [2,3] blunt abdominal trauma [4], 3 related to penetrating injury and 1 case in an infant caused by intense coughing [5]. In adult patients, this condition is usually caused by trauma (including iatrogenic perforation), and spontaneous perforation which etiology remains uncertain [6]. Most of the spontaneous cases have been reported in elderly patients associated with chronic rectal prolapse and an event of sudden increase of abdominal pressure [7][8][9].…”
Section: Introductionmentioning
confidence: 99%